4CPS-209 Experience of the nocebo effect in patients with switch to biosimilars in rheumatoid arthritis. Issue 1 (23rd March 2023) - Fresquet, R; María Ángeles, AB; Pascual, O; Gracia, R; Sopena, L; Varela, I; Gomez, P; Merchan, A; Bonaga, B
Abstract : Background and Importance: The nocebo effect is described as the worsening of associated symptoms or an increase in adverse effects due to a negative attitude towards a particular drug or pharmacological therapy, in this case biosimilar treatment. Lack of patient knowledge and discrepancies in the information provided are the main causes of negative expectations with biosimilars and their exchange with the original drug. Aim and Objectives: Study of the nocebo effect in patients with spondyloarthropathy and psoriatic arthritis after switching from the original drug to the biosimilar of adalimumab in a tertiary hospital. Material and Methods: Retrospective and observational study from January 2020 to October 2021. Clinical information was obtained from the electronic medical record. The following clinical and demographic variables were recorded: age, sex, medication, type of adverse reaction, adherence, and follow-up after the change. Results: During the study period, 66 switches were made from Humira® (original drug) to Hyrimoz® (biosimilar), with 72% biosimilar use in this clinical context. In 4% (3 patients) of the switches, a clinical worsening was observed at 6 months, the mean age was 46 years, male. Adherence to treatment (Hyrimoz) was over 90%. The most frequent symptoms were: skin symptoms with pruritus, axial clinical worsening, morning arthralgias. In all cases, and after discussion with the prescribing physician, it was decided to switch to the original brand. After returning to the reference brand, the patients presented an improvement of the symptomatology associated with the change to the biosimilar drug. Conclusion and Relevance: The nocebo effect is an uncommon effect, but it causes an increase in pharmaceutical expenditure, as well as in medical visits and complementary tests. Due to the small sample size, clinical worsening cannot be associated with the nocebo effect in this study. Therefore, further research on this topic is required. It may also lead to the administration of new drugs to counteract the symptoms caused by the nocebo effect. Better education of both healthcare professionals and patients on the knowledge of biosimilars can help reduce the likelihood of triggering a nocebo effect. References: Horta-Baas G. Patient-reported outcomes in rheumatoid arthritis: a key consideration for evaluating biosimilar uptake? Patient Relat Outcome Meas . 2022 Mar 30;13 :79–95. doi: 10.2147/PROM.S256715. Conflict of Interest: No conflict of interest